Análise da eficiência do regime de metas de inflação: um estudo em países da América Latina - Ellwanger, Kim (Universidade do Vale do Rio dos Sinos, 2016)
The objective of this study is to investigate the monetary policy performance with inflation targeting regime in five Latin American countries, between 2002 and 2014. The countries are Brazil, Chile, Colombia, Mexico and Peru. Inflation rates have been low and real economic variables, such as economic growth and the unemployment rate, have been satisfactory. A vector error correction model (VAR / VEC) is estimated for each country, with the aim of analyzing the impact of the interest rate on the other variables. The empirical evidence in this study suggests that, for Brazil and Chile, the exchange rate is an important transmission channel for monetary policy. According to the analysis of variance decomposition, the factors that influence the inflation rate are different for the five economies. The analyses in the inflation rate reveals that the interest rate is important to explain the inflation rate in Brazil and Mexico; however, in Chile, Mexico and Peru inflation rate is strongly associated with its own dynamics. The interest rate has proven to be more effective in Chile, Mexico and Peru to control and reduce inflationary pressures. During the period, the countries obtained significant gains in terms of economic growth, reduction of the unemployment rate, and the inflation rate has been controlled it. Indicating that this monetary regime has presented positive results for the selected economies.
Keywords: Regime de metas de inflação; Modelo VAR/VEC; América Latina; Inflation target regime; Model VAR / VEC; Latin America; ACCNPQ::Ciências Sociais Aplicadas::Economia